Torn between two targets: German police officers talk about the use of force - Klukkert, Astrid (2008)
Considering earlier research into police use of force as well as the judicial and practical frame of police work in Germany, the article presents the results of an empirical study on the individual and collective legitimization of the use of force by German police officers. There are numerous justifications for the use of force expressed by focus group participants in eight German Federal States who were responding to a hypothesized scenario. In the discussions observed within the groups, reference is first made to the state’s duty to prosecute alleged offences and the measures or formal actions to do this—hence, the legal authority to use force. In the course of the discussions, however, it became obvious that illegal violence may occur, although it was not perceived as such by the officers. Overall, and after an intensive analysis of the focus group discussions, it can be stated that use of force (whether legal or not) depends on the police officer’s perception of the resistance